PRODUKTIVITAS ALAT TANGKAP BAGAN PERAHU KM BAKTI FORTUNA 30 GT DI PERAIRAN PANTAI BARAT SIBOLGA - Chris Hadinata; Jonny Zain; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was held in December 2015 in KM Bakti Fortuna 30 GT on the West Coast Aquatic Sibolga. The purpose of this study is to (1) assess the sustainability of fishing effort through productivity value chart boats catching charts boat (2) determine the species composition of the catch and the frequency of appearance of the catch. This study uses a case study on one unit of fishing gear boat chart with the data taken directly. The results showed that the total catch of 7.76 tonnes / trip with catches productivity value obtained at 647.33 kg / day with an average catch of 517.87 kg / surgery setting. Production of this armada is higher than national standard productivity of Bagan perahu is 3,6 tonnes/trip The highest productivity of Bagan perahu on day 0,014 kg/m3minutes. There are 2 types of fish are caught with the frequency of appearance of the dominant species of fish caught that squid (Loligo sp).Keywords : Bagan Perahu, compotition, frequensy, production, productivity